Mechanism of slag-based silicate fertilizer suppressing methane emissions from paddies. (1st November 2022) - Das, Suvendu; Jena, Satya Narayan; Islam Bhuiyan, Mohammad Saiful; Kim, Gil Won; Kim, Pil Joo
Abstract: The addition of electron acceptors to boost soil microbes competitive to methanogens could minimize methane (CH4 ) emissions from paddy soils. To study the microbiological mechanisms underlying the suppression of CH4 emissions, silicate fertilizer made from blast furnace slag that contains electron acceptors, such as Fe, was applied to Japonica and Indica rice at a rate of 2 Mg ha −1 . We found that silicate fertilization significantly reduced CH4 emissions from Japonica and Indica rice by 21.1% and 25.7%, respectively, and the decrease in CH4 emissions coincided with an increase in iron reduction in paddy soils. Silicate fertilization markedly suppressed several methanogens and abundance of genes involved in acetoclastic and hydrogenotrphic methanogenesis, albeit the suppression of acetoclastic gene abundance was larger. Conversely, it increased methanotrophs, their gene abundance, and CH4 oxidation potential of paddy soils, which could be explained by an increase in root oxidation potential. Iron-reducing and oxidizing microbes, and their gene abundance significantly increased by silicate fertilization. Structural equation modeling showed that the suppression of CH4 emissions was mainly due to the competitive inhibition of methanogens by iron-reducing bacteria and the proliferation of methonotrophs. These findings have implications for understanding the CH4 biogeochemistry under silicate fertilization, as it has the potential to mitigate CH4 emissions from paddies. Graphical abstract: Image 1 Highlights: Fertilization with silicates suppressed CH4 emissions while increasing rice yields. Competative inhibition of methanogens by iron-reducers suppressed CH4 emissions. Increased methanotrophs reduces CH4 emissions from silicate-amended paddies. CH4 abatement by silicate could make slag a value-added product.